PENGGUNAAN VISUAL RETORIKA OLEH FOTOGRAFER DALAM PROSES PENYAMPAIAN PESAN MELALUI FOTO HUMAN INTEREST - Rizki Kurnia Illahi; Nita Rimayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Human Interest Photos is a photo that tells about social criticism and is a photo that contains many social values in it. The phenomenon that occurs in this study shows how a photographer manages photo interest to create a message using symbols, colors, and components displayed in the photo frame.This research uses qualitative method, with shortlist Visual Rhetorical analysis. Subjects focused on photographers as communicators in creating messages, Photography enthusiasts viewed from the use of subject / content,, perspective, and photography enthusiasts as audiences / contexts that explain how photographers use visual rhetoric to create messages on human interest photos. The research object used is Irving Lubis's human interest photo which is curated by www.fine-artportugal.com.The results of this study show that Irving Lubis's human interest photo creates a different message in the view of every audience influenced by the audience's own perspective. Photo by Irving Lubis tells about the criticism of social values in society, government, and change the perception of audience.Keywords : Uses of Visual Retorics, Human Interest, Photography analysis